2023
DOI: 10.3390/healthcare11111570
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Levels, Eating Habits, and Well-Being Measures in Students of Healthcare Degrees in the Second Year of the COVID-19 Pandemic

José Luis Maté-Muñoz,
Juan Hernández-Lougedo,
Jaime Ruiz-Tovar
et al.

Abstract: Background: When the first cases of COVID-19 (caused by SARS-CoV-2 virus infection) were discovered, exceptional norms to fight the spread of the virus were established by applying movement restrictions (lockdown) in many countries. These unprecedented norms led to sedentary behaviours and less healthy diets which could persist for much longer after lockdown. The aim of this study was to analyse the physical activity, eating habits, self-perceived well-being, and toxic habits, as well as the perceived changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The present study agrees with Bou-Hamad et al ( 21 ), who found that approximately two-thirds (63.5%) of their participants adopted a healthy diet during the pandemic. Maté-Muñoz et al ( 22 ) also mention a healthy change in eating habits compared to 12 months before the COVID-19 pandemic. Monteiro and Ferreira-Pêgo ( 23 ), when comparing eating habits during confinement compared to the normal semester of classes, found that the former was “better”; however, it is closely followed in percentage by the category being “the same.” On the other hand, Eşer et al ( 24 ) indicate that they found changes in the order of meals in students during their distance education, with 31.7% who regularly consumed their main meals followed by 31.2% who jumped.…”
Section: Discussionmentioning
confidence: 99%
“…The present study agrees with Bou-Hamad et al ( 21 ), who found that approximately two-thirds (63.5%) of their participants adopted a healthy diet during the pandemic. Maté-Muñoz et al ( 22 ) also mention a healthy change in eating habits compared to 12 months before the COVID-19 pandemic. Monteiro and Ferreira-Pêgo ( 23 ), when comparing eating habits during confinement compared to the normal semester of classes, found that the former was “better”; however, it is closely followed in percentage by the category being “the same.” On the other hand, Eşer et al ( 24 ) indicate that they found changes in the order of meals in students during their distance education, with 31.7% who regularly consumed their main meals followed by 31.2% who jumped.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lower levels of MD compliance were observed in those students with elevated stress and lower sleep quality [66]. Another study has indicated that the quarantine has exerted considerably negative effects on eating behaviors and physical activity [67]. The above has been attributed to the fact that there has been an elevation in food intake and a decrease in physical activity, which can result in body weight elevation [67].…”
Section: Discussionmentioning
confidence: 99%
“…Another study has indicated that the quarantine has exerted considerably negative effects on eating behaviors and physical activity [67]. The above has been attributed to the fact that there has been an elevation in food intake and a decrease in physical activity, which can result in body weight elevation [67]. In a longitude study conducted on 1520 participants, increased intake of cereals was related to decreased risk of COVID-19 infection, while the probability of being infected with COVID-19 reduced in combination with increasing olive oil consumption [68].…”
Section: Discussionmentioning
confidence: 99%